PSHREG: A SAS macro for proportional and nonproportional subdistribution hazards regression. Issue 2 (February 2015) - Kohl, Maria; Plischke, Max; Leffondré, Karen; Heinze, Georg
Highlights The %pshreg SAS macro fits Fine-Gray models for competing risks. The macro first modifies a given data set and then uses PROC PHREG for analysis. Many useful features of PROC PHREG can now be applied to a Fine-Gray model. Time-dependent effects can be accommodated by time-by-covariate interactions. For small data sets, the Firth correction is available.